Mixed method approach in designing flight decks with touch screens: a framework - Avsar, Huseyin; Fischer, Joel E.; Rodden, Tom (2016)
Touch screen technology’s first public appearance was in the early 2000s. Touch screens became a part of the daily life with the invention of smartphones and tablets. Now, this technology has the potential to be the next big change in flight deck design. To date, mobile devices are deployed by several air carriers to perform a host of non-safety critical pre-flight and in-flight tasks. Due to high safety requirements requested by authorities, new technologies cannot be adopted as fast as in other settings. Flight deck evolution, which is briefly presented in this paper, is reflecting this natural time delay. Avionics manufacturers are exploring and working on future concepts with touch screen displays. This paper investigates the potential benefits and challenges of touch screen technology on flight decks by means of a variety of qualitative and quantitative research methods (mixed method approach). On the basis of this, a framework was constructed showing the relation between various aspects that could impact the usability of touch screens on the flight deck. This paper concludes with a preliminary questionnaire that can help avionic designers to evaluate whether a touch screen is an appropriate user interface for their system.